Sol-gel assisted molten-salt synthesis of novel single phase Y3–2xCa2xTaxAl5−xO12:1%Eu garnet structure phosphors - Skruodiene, Monika; Juodvalkyte, Ruta; Inkrataite, Greta; Pakalniskis, Andrius; Ramanauskas, Rimantas; Sarakovskis, Anatolijs; Skaudzius, Ramunas (Elsevier Ltd, 2022)
Strong absorption and emission are the key the features of any phosphor. The results obtained during this study demonstrate the difficulty of the incorporation of tantalum ions into the garnet structure and reveal that only the combination of Sol-Gel synthesis method together with Molten-Salt technique enable to obtain a single-phase cubic garnet structure. Note that, the Sol-Gel synthesis assisted by further processing by Molten-Salt technique can be a potentially new way of material preparation reported in literature. This work also proves that this combination of synthesis methods is much more capable of incorporating ions with large ionic radii into the garnet structure as compared to traditional Sol-Gel method. Moreover, samples synthesized using this new technique exhibit 30% higher emission intensities as compared to the ones prepared by the original Sol-Gel method, while also reducing the needed sintering temperature by 200 °C. To the best of our knowledge, the modification of yttrium aluminum garnet (Y3Al5O12, YAG) by co-doping it with Ca2+ and Ta5+ ions by Sol-Gel assisted Molten-Salt route has been investigated for the first time. --//-- Monika Skruodiene, Ruta Juodvalkyte, Greta Inkrataite, Andrius Pakalniskis, Rimantas Ramanauskas, Anatolijs Sarakovskis, Ramunas Skaudzius, Sol-gel assisted molten-salt synthesis of novel single phase Y3–2xCa2xTaxAl5−xO12:1%Eu garnet structure phosphors, Journal of Alloys and Compounds, Volume 890, 2022, 161889, ISSN 0925-8388, https://doi.org/10.1016/j.jallcom.2021.161889. Article published under the CC BY license.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; YAG; Ca2+ and Ta5+ doped yttrium aluminum garnet; luminescence; Co-doping; charge compensation